A positive electrode sheet, a method for manufacturing the same, and a battery
Patent Information
- Application Number
- CN202611294959.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]为了解决现有磷酸铁锂-三元材料混合体系因颗粒形貌、粒径及表面特性差异大而导致浆料分散不均、极片内部微观结构一致性差,以及三元材料在高压实条件下易发生颗粒破碎和过渡金属溶出,进而导致电池功率性能不足和循环稳定性差的技术问题,本发明核心提供了一种正极极片,通过对两种三元材料及磷酸铁锂材料的颗粒形貌、粒径分布及钴含量等关键参数进行差异化设计,有效改善了电池的功率性能和循环稳定性,使电池在5C倍率下的放电能力达到95%以上,在1C/1C充放电条件下容量保持率降至80%时的循环次数达到3000次以上,能够满足高功率、长寿命应用场景的需求
(1)本发明通过将正极极片设置为双层涂层结构,第一正极涂层含磷酸铁锂材料和三元材料A、第二正极涂层含三元材料B,使两种涂层功能分化、协同增效,改善了电池的综合性能;
Smart Images

Figure CN123017876A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery technology, and in particular to a positive electrode sheet, its preparation method, and a battery. Background Technology
[0002] Lithium-ion batteries have been widely used in consumer electronics, electric vehicles, and energy storage systems due to their advantages such as high energy density, long cycle life, and environmental friendliness. With the continuous expansion of application scenarios, the market demand for the energy density of lithium-ion batteries is increasing.
[0003] Lithium iron phosphate (LFP) materials are widely used due to their stable structure, low cost, and excellent safety performance; however, their energy density is gradually approaching its theoretical limit. Introducing ternary layered oxide materials (such as lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide) into the LFP system has become an effective way to improve battery energy density. However, simple physical mixing of ternary materials and LFP (i.e., blending systems) faces insufficient power performance in practical applications. The main reasons are: firstly, there are significant differences in particle morphology, particle size distribution, and surface characteristics between ternary materials and LFP, making it difficult to achieve uniform dispersion during slurry preparation and coating, resulting in poor microstructure consistency within the electrode and obstructed lithium-ion transport paths; secondly, ternary materials are prone to particle breakage and transition metal dissolution during cycling, especially under high compaction density conditions, which further accelerates battery capacity decay. To alleviate these problems, existing technologies have attempted to improve the process by optimizing mixing processes and adjusting binder systems, but the effects are limited, and a good balance between energy density, power performance, and cycle life remains difficult to achieve. Summary of the Invention
[0004] To address the technical problems of uneven slurry dispersion and poor microstructure consistency within the electrode due to significant differences in particle morphology, size, and surface characteristics in existing lithium iron phosphate-ternary material hybrid systems, as well as the tendency for ternary materials to break down and dissolve transition metals under high compaction conditions, leading to insufficient battery power performance and poor cycle stability, this invention provides a positive electrode. By differentiating key parameters such as particle morphology, particle size distribution, and cobalt content of the two ternary materials and lithium iron phosphate material, this invention effectively improves the battery's power performance and cycle stability. The battery achieves a discharge capacity of over 95% at 5C rate and over 3000 cycles when the capacity retention drops to 80% under 1C / 1C charge / discharge conditions, meeting the demands of high-power, long-life applications.
[0005] The first aspect of the present invention provides a positive electrode sheet, the positive electrode sheet comprising: current collector; A first positive electrode coating is disposed on at least one side surface of the current collector along the thickness direction; the first positive electrode coating comprises lithium iron phosphate material and ternary material A. A second positive electrode coating is disposed on the surface of the first positive electrode coating away from the current collector; the second positive electrode coating comprises ternary material B.
[0006] Optionally, the positive electrode sheet satisfies at least one of the following conditions: (1) The sphericity of the ternary material A is greater than that of the ternary material B; (2) The angle of repose of the ternary material A is smaller than that of the lithium iron phosphate material, and the difference between the two is 10°~20°; (3) The D of the lithium iron phosphate material V 50 particles with a diameter smaller than that of the ternary material B V 50 particle size; (4) The D of the ternary material B V 50 particles with a diameter less than or equal to that of the ternary material A V 50 particle size.
[0007] Optionally, the positive electrode sheet satisfies at least one of the following conditions: (1) The sphericity of the ternary material A is 0.8~1; (2) The angle of repose of the ternary material A is 20°~30°; (3) The D of the ternary material A V 50 particles have a diameter of 5μm to 8μm; (4) The angle of repose of the lithium iron phosphate material is 30°~50°; (5) The D of the lithium iron phosphate material V 50 particles have a diameter of 0.5μm to 2μm; (6) The sphericity of the ternary material B is 0.6~0.8; (7) The D of the ternary material B V The particle size of 50 particles is 2μm~5μm.
[0008] Optionally, both ternary material A and ternary material B are cobalt-containing ternary materials, and satisfy at least one of the following conditions: (1) The cobalt content in the ternary material A is lower than the cobalt content in the ternary material B; (2) The cobalt content in the ternary material A is 4 mol% to 8 mol% of the total metal content excluding Li in the ternary material A. (3) The cobalt content in the ternary material B is 8 mol% to 12 mol% of the total amount of metals other than Li in the ternary material B.
[0009] Optionally, the chemical formula of both ternary material A and ternary material B is Li. a Ni b Co c M d N e O f ; Wherein, 0.6≤a≤1.1, 0.5≤b≤0.95, 0.04≤c≤0.12, 0.01≤d≤0.35, 0.001≤e≤0.01, 1.9≤f≤2.1, and b+c+d+e=1, M includes at least one of Mn and Al, and N includes one or more combinations of Mg, Sr, B, Ca, Na, K, Sn, Cu, Ti, Nb, La, Bi, and Zr.
[0010] Optionally, the lithium iron phosphate material includes a lithium iron phosphate body and a carbon coating layer covering the surface of the lithium iron phosphate body; The lithium iron phosphate material satisfies at least one of the following conditions: (1) The mass of the carbon coating layer is 1wt%~2wt% of the mass of the lithium iron phosphate material; (2) The mass of the lithium iron phosphate material is 60wt% to 90wt% of the sum of the masses of the ternary material A and the lithium iron phosphate material.
[0011] Optionally, the lithium iron phosphate material contains doping elements, and the lithium iron phosphate material satisfies at least one of the following conditions: (1) The lithium iron phosphate body contains doped elements; (2) The carbon coating layer contains doped elements; (3) The doping element includes a metallic element; (4) The doping element is selected from at least one of Ti, V, Zr, Mn, Mg, and Al; (5) The doping elements include non-metallic elements; (6) The doping element is selected from at least one of Si, F, N, and Cl; (7) The doping amount of the doping element in the lithium iron phosphate material is 500ppm~3000ppm.
[0012] Optionally, the positive electrode sheet satisfies at least one of the following conditions: (1) The thickness of the first positive electrode coating is greater than the thickness of the second positive electrode coating; (2) The thickness of the first positive electrode coating is 75μm~100μm; (3) The thickness of the second positive electrode coating is 35μm~60μm.
[0013] A second aspect of the present invention provides a method for preparing a positive electrode sheet, wherein the positive electrode sheet is prepared by step-by-step coating or co-coating. The step-by-step coating process includes: Lithium iron phosphate material, ternary material A, first binder, first conductive agent and dispersant are mixed evenly to obtain the first positive electrode slurry; The first positive electrode slurry is coated onto the surface of the current collector and dried to obtain the first positive electrode coating. Ternary material B, second binder, and second conductive agent are mixed evenly to obtain the second positive electrode slurry; The second positive electrode slurry is coated onto the surface of the first positive electrode coating away from the current collector, and then dried and rolled to obtain the positive electrode sheet; The co-coating process includes: Lithium iron phosphate material, ternary material A, first binder, first conductive agent and dispersant are mixed evenly to obtain the first positive electrode slurry; Ternary material B, second binder, and second conductive agent are mixed evenly to obtain the second positive electrode slurry; Using a multi-layer extrusion coating die, the first positive electrode slurry and the second positive electrode slurry are simultaneously extruded and coated onto the surface of the current collector; after drying, the current collector, the first positive electrode coating and the second positive electrode coating are obtained in sequence, and after rolling, the positive electrode sheet is obtained.
[0014] A third aspect of the present invention provides a battery comprising a positive electrode sheet as described above or a positive electrode sheet prepared by the preparation method described above.
[0015] Beneficial effects: This invention provides a positive electrode sheet, its preparation method, and a battery, which have the following advantages: (1) The present invention sets the positive electrode sheet into a double-layer coating structure, the first positive electrode coating contains lithium iron phosphate material and ternary material A, and the second positive electrode coating contains ternary material B, so that the two coatings have different functions and synergistic effect, thereby improving the overall performance of the battery. (2) By controlling the sphericity of ternary material A to be higher than that of ternary material B, the first positive electrode coating obtains higher tap density and compaction density to improve energy density, and the second positive electrode coating forms a moderate porosity to improve electrolyte wetting and rate performance. (3) By controlling the difference between the angle of repose of ternary material A and the angle of repose of lithium iron phosphate material to be 10°~20°, the present invention improves the dispersion uniformity of the two particles, suppresses the coating of lithium iron phosphate on ternary material A and the particle breakage during the rolling process, and extends the cycle life of the battery. (4) By controlling the particle size of ternary material A to 5μm~8μm, the particle size of lithium iron phosphate material to 0.5μm~2μm, and the particle size of ternary material B to 2μm~5μm, the present invention achieves a balance between compaction density, rate performance and anti-breakage ability of each layer of material.
[0016] (5) By setting the cobalt content (4mol%~8%) of ternary material A to be lower than the cobalt content (8mol%~12%) of ternary material B, the present invention reduces the amount of cobalt used in the first cathode coating while ensuring the interfacial reaction activity of the second cathode coating, thus balancing electrochemical performance and material cost. (6) This invention improves the electronic conductivity and enhances the rate performance of the battery by setting a carbon coating layer (1wt%~2wt%) on the lithium iron phosphate material and introducing doping elements (500ppm~3000ppm). (7) By controlling the proportion of lithium iron phosphate material in the mixed active material to 60wt%~90wt%, the present invention takes into account the safety performance, energy density and rate performance of the battery. (8) By setting the thickness of the first positive electrode coating (75μm~100μm) to be greater than the thickness of the second positive electrode coating (35μm~60μm), the present invention enables the first positive electrode coating to fully play its role in supporting the safety structure, and the second positive electrode coating to fully play its advantages in interfacial dynamics, thereby achieving a balance between safety performance and power performance. (9) The preparation method provided by the present invention can be achieved by step coating or co-coating, which has strong process flexibility, adapts to different production line conditions, and has good prospects for industrial application. Attached Figure Description
[0017] Figure 1 This is a schematic diagram of the structure of the positive electrode sheet of the present invention; Figure 1 In the diagram, 1-first positive electrode coating, 2-second positive electrode coating, 3-ternary material A, 4-lithium iron phosphate material, 5-ternary material B, 6-current collector. Detailed Implementation
[0018] To make the technical solution and beneficial effects of this application more apparent and understandable, a detailed description is provided below by listing specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional experimental conditions. Unless otherwise specified, all reagents and raw materials used in this application are commercially available.
[0019] In the following description, numerous specific details are set forth in order to provide a more thorough understanding of this application. However, it will be apparent to those skilled in the art that this application can be practiced without one or more of these details. In other instances, to avoid confusion with this application, some technical features well-known in the art have not been described; that is, not all features of actual embodiments are described herein, nor are well-known functions and steps described in detail.
[0020] It should be noted that the relational terms (such as first and second) used in the description of this application are only used to distinguish one entity / operation from another entity / operation, and do not necessarily require or imply that there is an actual relationship or order between these entities / operations; in specific implementation, the principle of meeting actual use needs should be followed.
[0021] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0022] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0023] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0024] The first aspect of the present invention provides a positive electrode sheet, the positive electrode sheet comprising: current collector; A first positive electrode coating is disposed on at least one side surface of the current collector along the thickness direction; the first positive electrode coating comprises lithium iron phosphate material and ternary material A. A second positive electrode coating is disposed on the surface of the first positive electrode coating away from the current collector; the second positive electrode coating comprises ternary material B.
[0025] Studies have found that while mixing lithium iron phosphate (LFP) with ternary materials can effectively improve energy density in the lithium-ion battery field, the significant differences in particle morphology, particle size, and surface characteristics between the two lead to uneven slurry dispersion and poor consistency in the internal microstructure of the electrode. Furthermore, ternary materials are prone to particle breakage and transition metal dissolution under high compaction conditions, which further degrades the battery's rate performance and cycle life. To address these issues, this invention provides a positive electrode with a dual-layer coating structure, comprising a current collector, a first positive electrode coating disposed on the surface of the current collector, and a second positive electrode coating disposed on the surface of the first positive electrode coating. The first positive electrode coating comprises LFP material and ternary material A, and the second positive electrode coating comprises ternary material B. By combining lithium iron phosphate material with ternary material A in the first positive electrode coating to provide safety support and basic capacity, while using only ternary material B in the second positive electrode coating near the separator to achieve high rate capability and interface stability, the two coatings have different functions and work synergistically. This overcomes the problems of uneven particle dispersion and severe interfacial side reactions in simple mixed systems, while also taking into account the battery's safety, energy density, rate performance and cycle life.
[0026] Optionally, the positive electrode sheet satisfies at least one of the following conditions: (1) The sphericity of the ternary material A is greater than that of the ternary material B; (2) The angle of repose of the ternary material A is smaller than that of the lithium iron phosphate material, and the difference between the two is 10°~20°; (3) The D of the lithium iron phosphate material V 50 particles with a diameter smaller than that of the ternary material B V 50 particle size; (4) The D of the ternary material B V 50 particles with a diameter less than or equal to that of the ternary material A V 50 particle size.
[0027] The "sphericity" involved in this invention refers to a dimensionless index used to characterize the degree to which the shape of positive electrode active material particles approximates a sphere; it is defined as the ratio of the particle's projected area to the area of its smallest circumscribed circle, or, using the Wadell sphericity definition known in the art (i.e., the ratio of the surface area of a sphere with the same volume as the particle to the actual surface area of the particle); the closer the particle shape is to a perfect sphere, the closer its sphericity value is to 1. In this invention, the sphericity is preferably obtained by statistical analysis of the particle's projected profile using scanning electron microscopy (SEM) combined with image analysis software.
[0028] This invention optimizes electrode performance by limiting the sphericity relationship between ternary material A in the first positive electrode coating and ternary material B in the second positive electrode coating. Specifically, ternary material A with high sphericity and large particle size is selected in the first active layer, resulting in higher tap density, compaction density, and specific capacity, which is beneficial for improving the energy density of the first active layer. In the second active layer, ternary material B with relatively low sphericity (0.6~0.8) and smaller particle size is selected, resulting in lower compaction density, which helps to form a reasonable electrode porosity to improve electrolyte wetting and rate performance. At the same time, the small particle size material has strong compressive strength, which can reduce particle breakage during the rolling process, thereby improving cycle performance. This invention achieves synergistic optimization of energy density and power performance through differentiated control of the sphericity of the two ternary materials.
[0029] The "angle of repose" involved in this invention refers to the maximum angle formed between the free-stacking slope of a powder material and the horizontal plane under natural stacking conditions. This parameter is an important physical indicator characterizing the flowability, internal friction, and interparticle interaction of powder. Generally, the higher the sphericity of the particles and the smoother the surface, the smaller the angle of repose and the better the flowability of the powder; conversely, the irregular shape, rough surface, or small particle size of the particles result in a larger angle of repose. In this invention, the angle of repose is preferably measured using the injection method or the discharge method. Specifically, the injection method can be used for testing and determination in GB / T 11986-1989 "Measurement of Angle of Repose of Surfactant Powders and Particles".
[0030] This invention limits the angle of repose of ternary material A to be smaller than that of lithium iron phosphate material, with the difference being 10°~20°. Lithium iron phosphate material with smaller particle size inherently has a larger angle of repose, while ternary material A, with higher sphericity, has a lower angle of repose. This invention controls the difference in angle of repose between the two within the range of 10°~20°. A larger difference in angle of repose is beneficial for improving the dispersion uniformity of the two types of particles in the slurry and electrode, increasing the friction between lithium iron phosphate particles to suppress excessive coating of the ternary material surface, and simultaneously reducing particle breakage and over-release of the ternary material during rolling, thereby balancing electrode compaction density and cycle stability.
[0031] The "D" involved in this invention V "50-particle size" (i.e., volume average median diameter) refers to the particle size value corresponding to 50% of the cumulative volume in a cumulative particle size distribution curve based on a volume reference, measured using laser diffraction or similar particle size analysis techniques. In other words, D... V 50 is the critical particle size at which the cumulative volume percentage of all test particles arranged in ascending order of particle size is exactly 50%. This value is also commonly referred to in the art as the "median diameter" or "median particle size". In this invention, D VThe 50 value can be measured by dispersing the positive electrode material powder in a suitable solvent (such as water or ethanol), using a laser particle size analyzer, and taking the volume distribution statistical results as the standard.
[0032] This invention also specifies lithium iron phosphate material, ternary material A, and ternary material B as D. V 50mm particle size to optimize coating structure; preferably set D of lithium iron phosphate material V 50 particles smaller than ternary material B in D V 50 particles ≤ ternary material A's D V For lithium iron phosphate materials with a particle size of 50 μm, insufficient grain growth due to excessively small particle size can lead to low specific capacity, while excessively large particle size can easily result in deteriorated rate performance. Through analysis of three materials... V The synergistic constraint of 50mm particle size optimizes the spatial arrangement and lithium-ion transport channels within the electrode at the microscale, providing a structural basis for achieving high energy density, high power density, and long lifetime.
[0033] Optionally, the positive electrode sheet satisfies at least one of the following conditions: (1) The sphericity of the ternary material A is 0.8~1; it can be listed as 0.8, 0.85, 0.9, 0.95, 1, etc.; (2) The angle of repose of the ternary material A is 20°~30°; it can be listed as 20°, 21°, 22°, 23°, 24°, 25°, 26°, 27°, 28°, 29°, 30°, etc. (3) The D of the ternary material A V 50. Particle size ranges from 5μm to 8μm; examples include 5μm, 6μm, 7μm, 8μm, etc. (4) The angle of repose of the lithium iron phosphate material is 30°~50°; it can be listed as 30°, 31°, 32°, 33°, 34°, 35°, 36°, 37°, 38°, 39°, 40°, 41°, 42°, 43°, 44°, 45°, 46°, 47°, 48°, 49°, 50°, etc. (5) The D of the lithium iron phosphate material V The particle size ranges from 0.5μm to 2μm; examples include 0.5μm, 1.0μm, 1.5μm, and 2μm. (6) The sphericity of the ternary material B is 0.6~0.8; it can be listed as 0.6, 0.65, 0.7, 0.75, 0.8, etc. (7) The D of the ternary material B V The particle size of 50 particles ranges from 2μm to 5μm; examples include 2μm, 3μm, 4μm, and 5μm.
[0034] This invention further defines the sphericity, angle of repose, and D of the three active materials. V 50 particle size range. On the one hand, the preferred ternary material A has a sphericity of 0.8~1, an angle of repose of 20°~30°, and D... V The particle size of 50 particles ranges from 5μm to 8μm, ensuring that ternary material A has a good spherical morphology and a large particle size, resulting in higher tap density and compaction density, which is beneficial for improving the energy density of the first cathode coating; on the other hand, the preferred repose angle of lithium iron phosphate material is 30°~50°, D V The particle size of 50 is 0.5μm~2μm. The smaller particle size, combined with a larger angle of repose, allows the difference in angle of repose between it and ternary material A to be controlled within the range of 10°~20°. This improves the dispersion uniformity of the two particles in the slurry and electrode, suppresses the coating of lithium iron phosphate on the surface of ternary material A, and inhibits particle breakage during the rolling process. Furthermore, the sphericity of ternary material B can be preferably selected as 0.6~0.8, D... V The particle size of the 50 particles, ranging from 2μm to 5μm, allows the second cathode coating to form a suitable electrode porosity after rolling, facilitating electrolyte wetting and rapid lithium-ion transport. Simultaneously, the smaller particle size provides stronger compressive strength, reducing particle breakage and interfacial side reactions under high-compaction conditions, thereby improving the battery's cycle stability. In summary, by synergistically limiting the parameters of the three materials mentioned above, the first cathode coating focuses on contributing to energy density and safety performance, while the second cathode coating focuses on contributing to rate performance and cycle stability. Their complementary functions result in a significant improvement in the overall battery performance.
[0035] Further optionally, the positive electrode sheet simultaneously satisfies conditions (1) to (7).
[0036] Optionally, both ternary material A and ternary material B are cobalt (Co)-containing ternary materials, and satisfy at least one of the following conditions: (1) The cobalt content in the ternary material A is lower than the cobalt content in the ternary material B; (2) The cobalt content in the ternary material A is 4 mol% to 8 mol% of the total metal content excluding Li in the ternary material A. (3) The cobalt content in the ternary material B is 8 mol% to 12 mol% of the total amount of metals other than Li in the ternary material B.
[0037] In this invention, both ternary material A and ternary material B are cobalt-containing ternary materials. Cobalt primarily functions to improve electronic conductivity and stabilize the crystal structure of ternary materials, thereby enhancing their cycling stability. However, excessively high cobalt content significantly increases raw material costs and deteriorates the material's specific capacity, while excessively low cobalt content worsens the material's kinetic properties and cycling performance. Therefore, the cobalt content needs to be controlled within a reasonable range. Based on these considerations, this invention further differentiates the cobalt content of the two ternary materials: the molar ratio of cobalt content to the total metal content excluding Li in ternary material A is 4 mol% to 8 mol%, and the molar ratio of cobalt content to the total metal content excluding Li in ternary material B is 8 mol% to 12 mol%, with the cobalt content of ternary material A being lower than that of ternary material B. The basis for this differentiated design is that ternary material B is located in the second cathode coating, which directly contacts the electrolyte and preferentially undergoes lithium insertion / extraction reactions. Therefore, it requires a higher cobalt content to improve its kinetic performance and cycle stability. Ternary material A, on the other hand, is located in the first cathode coating, and is physically separated from the electrolyte by the second cathode coating. Reducing its cobalt content will not have a significant negative impact on the overall cycle performance of the battery, but it can effectively control material costs and avoid the adverse effects of high cobalt content on specific capacity. Therefore, by implementing a layered differentiated design for the cobalt content of ternary materials A and B, the design balances the capacity utilization of the first cathode coating and overall cost control while ensuring the interfacial reactivity and cycle stability of the second cathode coating.
[0038] Optionally, the chemical formula of both ternary material A and ternary material B is Li. a Ni b Co c M d N e O f ; Wherein, 0.6≤a≤1.1, 0.5≤b≤0.95, 0.04≤c≤0.12, 0.01≤d≤0.35, 0.001≤e≤0.01, 1.9≤f≤2.1, and b+c+d+e=1, M includes at least one of Mn and Al, and N includes one or more combinations of Mg, Sr, B, Ca, Na, K, Sn, Cu, Ti, Nb, La, Bi, and Zr. Ternary materials within this formula range can be well-matched with the aforementioned lithium iron phosphate materials and double-layer coating structures, contributing to further optimization of the battery's electrochemical performance.
[0039] Optionally, the lithium iron phosphate material includes a lithium iron phosphate body and a carbon coating layer covering the surface of the lithium iron phosphate body; The lithium iron phosphate material satisfies at least one of the following conditions: (1) The mass of the carbon coating layer is 1wt% to 2wt% of the mass of the lithium iron phosphate material; it can be listed as 1wt%, 1.2wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.8wt%, 2wt%, etc. (2) The mass of the lithium iron phosphate material is 60wt% to 90wt% of the sum of the masses of the ternary material A and the lithium iron phosphate material.
[0040] In this invention, the lithium iron phosphate material comprises a lithium iron phosphate substrate and a carbon coating layer covering the surface of the lithium iron phosphate substrate. The carbon coating layer improves the electronic conductivity of the lithium iron phosphate material, thereby enhancing the rate performance of the battery. However, the content of the carbon coating layer needs to be controlled within a reasonable range: if the carbon coating layer is too small, the electronic conductivity of the lithium iron phosphate material will be insufficient, and the rate performance of the battery will deteriorate significantly; if the carbon coating layer is too large, since the true density of the carbon layer is much lower than that of the lithium iron phosphate substrate, the compaction density of the material will be significantly reduced, thus affecting the overall compaction density of the electrode and the energy density of the battery. Based on the above considerations, this invention limits the mass of the carbon coating layer to 1wt%~2wt% of the mass of the lithium iron phosphate material. Within this range, it ensures that the lithium iron phosphate material has sufficient electronic conductivity to support good rate performance, while avoiding the degradation of the electrode compaction density due to excessive carbon layers.
[0041] Furthermore, this invention limits the mass percentage of lithium iron phosphate (LFP) material in the total amount of LFP material and ternary material A to 60 wt%~90 wt%. LFP material exhibits superior structural stability compared to ternary materials; a higher LFP percentage improves battery safety. However, LFP material has relatively low specific capacity and compaction density, and its lithium-ion channels are one-dimensional. Excessive LFP percentage restricts lithium-ion insertion and extraction rates, leading to deterioration in rate performance. Conversely, insufficient LFP percentage compromises battery safety. Maintaining the LFP percentage within the range of 60 wt%~90 wt% ensures both high energy density and good rate performance while guaranteeing battery safety, allowing the first cathode coating to fully leverage its structural support and safety features.
[0042] Optionally, the lithium iron phosphate material contains doping elements, and the lithium iron phosphate material satisfies at least one of the following conditions: (1) The lithium iron phosphate body contains doped elements; (2) The carbon coating layer contains doped elements; (3) The doping element includes a metallic element; (4) The doping element is selected from at least one of Ti, V, Zr, Mn, Mg, and Al; (5) The doping elements include non-metallic elements; (6) The doping element is selected from at least one of Si, F, N, and Cl; (7) The doping amount of the doping element in the lithium iron phosphate material is 500ppm~3000ppm; it can be listed as 500ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, etc.
[0043] In this invention, the lithium iron phosphate material is further improved by doping modification to enhance its electronic conductivity. Specifically, the lithium iron phosphate bulk and / or the carbon coating layer contain doping elements, meaning the doping elements can exist in the lithium iron phosphate bulk lattice, in the carbon coating layer, or both. The doping elements are selected from at least one metallic element from Ti, V, Zr, Mn, Mg, and Al, and / or at least one non-metallic element from Si, F, N, and Cl. These doping elements can effectively improve the electronic conductivity of the lithium iron phosphate material, but the doping amount needs to be controlled within a reasonable range: when the doping amount is too low, the improvement in electronic conductivity is insufficient, and the rate performance of the battery is still difficult to meet requirements; when the doping amount is too high, too many impurities and defects will be introduced into the lithium iron phosphate material, damaging the integrity of the crystal structure and leading to deterioration of cycle performance. Based on the above considerations, this invention limits the doping amount of the dopant element in the lithium iron phosphate material to 500ppm~3000ppm. Within this range, it can sufficiently improve electronic conductivity to enhance rate performance while avoiding the deterioration of cycle performance due to impurities introduced by excessive doping. The conductivity of the lithium iron phosphate material is synergistically optimized through surface coating and bulk doping, further ensuring the simultaneous improvement of battery rate performance and cycle performance.
[0044] Optionally, the positive electrode sheet satisfies at least one of the following conditions: (1) The thickness of the first positive electrode coating is greater than the thickness of the second positive electrode coating; (2) The thickness of the first positive electrode coating is 75μm~100μm; it can be listed as 75μm, 78μm, 80μm, 82μm, 85μm, 88μm, 90μm, 92μm, 95μm, 98μm, 100μm, etc. (3) The thickness of the second positive electrode coating is 35μm~60μm; it can be listed as 35μm, 38μm, 40μm, 42μm, 45μm, 48μm, 50μm, 52μm, 55μm, 58μm, 60μm, etc.
[0045] In this invention, the thickness of the first positive electrode coating is greater than that of the second positive electrode coating. Since the first positive electrode coating is closer to the current collector side and contains lithium iron phosphate material, its structural stability and thermal safety are superior to ternary materials. The thicker first positive electrode coating helps improve the battery's safety performance under abuse conditions. Conversely, the second positive electrode coating is closer to the separator side, and its relatively thinner thickness helps shorten the lithium-ion diffusion path and reduce interfacial impedance, thereby improving the battery's rate performance. Based on these considerations, this invention limits the thickness of the first positive electrode coating to 75μm~100μm and the thickness of the second positive electrode coating to 35μm~60μm. This differentiated design allows the first positive electrode coating to play a major safety structural support role inside the battery, while the second positive electrode coating fully utilizes its interfacial dynamic advantages due to its proximity to the separator. The two layers complement each other functionally, jointly achieving a balance between battery safety and power performance.
[0046] A second aspect of the present invention provides a method for preparing a positive electrode sheet, wherein the positive electrode sheet is prepared by step-by-step coating or co-coating. The step-by-step coating process includes: Lithium iron phosphate material, ternary material A, first binder, first conductive agent and dispersant are mixed evenly to obtain the first positive electrode slurry; The first positive electrode slurry is coated onto the surface of the current collector and dried to obtain the first positive electrode coating. Ternary material B, second binder, and second conductive agent are mixed evenly to obtain the second positive electrode slurry; The second positive electrode slurry is coated onto the surface of the first positive electrode coating away from the current collector, and then dried and rolled to obtain the positive electrode sheet; The co-coating process includes: Lithium iron phosphate material, ternary material A, first binder, first conductive agent and dispersant are mixed evenly to obtain the first positive electrode slurry; Ternary material B, second binder, and second conductive agent are mixed evenly to obtain the second positive electrode slurry; Using a multi-layer extrusion coating die, the first positive electrode slurry and the second positive electrode slurry are simultaneously extruded and coated onto the surface of the current collector; after drying, the current collector, the first positive electrode coating and the second positive electrode coating are obtained in sequence, and after rolling, the positive electrode sheet is obtained.
[0047] The second aspect of this invention also provides a method for preparing the aforementioned positive electrode sheet, which can be achieved by step-by-step coating or co-coating, offering high production flexibility. Step-by-step coating involves first forming a first positive electrode coating on the surface of a first current collector and drying it, then coating a second positive electrode coating onto that surface. Co-coating uses a multi-layer extrusion coating die to simultaneously extrude and coat the first and second positive electrode slurries onto the surface of the current collector, and a single drying cycle yields the double-layer coating structure. Both methods can achieve the aforementioned double-layer positive electrode sheet structure, and the choice can be made flexibly based on production line equipment conditions in actual production, ensuring good interfacial bonding between the first and second positive electrode coatings.
[0048] In some embodiments, the first adhesive and the second adhesive may include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), polyacrylonitrile (PAN), polyimide (PI), styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), sodium carboxymethyl cellulose (CMC), etc.
[0049] In some embodiments, the first conductive agent and the second conductive agent each independently include conductive carbon black (SP), carbon nanotubes (CNT), graphene, conductive graphite, acetylene black, Ketjen black, carbon fiber (VGCF), etc.
[0050] In some embodiments, the dispersant may include, for example, polyvinylpyrrolidone (PVP), polyethylene glycol (PEG), polyacrylamide (PAM), sodium dodecylbenzenesulfonate (SDBS), etc.
[0051] A third aspect of the present invention provides a battery comprising a positive electrode sheet as described above or a positive electrode sheet prepared by the preparation method described above.
[0052] Optionally, the 5C rate performance (5C discharge capacity / 1C discharge capacity × 100%) of the battery is 95% or higher; more preferably 96% or higher; indicating that the positive electrode of the present invention can impart good rate performance to the battery.
[0053] Optionally, the battery has more than 3,000 cycles when the capacity retention drops to 80% under 1C / 1C charge / discharge conditions; this indicates that the positive electrode of the present invention can give the battery excellent cycle stability.
[0054] The present invention does not impose any particular limitation on the negative electrode material in the battery, as long as it can achieve the purpose of reversible lithium insertion and extraction. For example, graphite, silicon-based materials, tin-based materials, lithium titanate, etc. can be used; in some embodiments, the negative electrode material is graphite.
[0055] This invention does not impose any particular limitation on the electrolyte in the battery, as long as it can ensure the normal transport of lithium ions between the positive and negative electrodes; the electrolyte includes a lithium salt and an organic solvent, and the lithium salt may include lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), etc.; in some embodiments, the lithium salt is lithium hexafluorophosphate; the organic solvent may include at least one of ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and propylene carbonate (PC), and in some embodiments, the organic solvent is a mixed solvent of EC, EMC and DMC, with a volume ratio of 1:1:1.
[0056] This invention does not impose any particular limitation on the material of the separator in the battery, as long as it can achieve electronic insulation and allow lithium ions to pass through. For example, polypropylene (PP) separator, polyethylene (PE) separator, PP / PE composite separator, polyimide separator or ceramic coated separator can be used.
[0057] This invention does not impose any particular limitations on the packaging form and manufacturing method of the battery. For example, the battery cells can be assembled using a stacking process or a winding process, and the packaging form can be a soft pack, a cylindrical or a square hard shell, etc. In some embodiments, the positive electrode, negative electrode and separator are assembled into a dry battery cell and then placed in an aluminum-plastic film shell. After baking, injecting electrolyte and performing capacity testing, a soft pack battery is obtained.
[0058] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0059] Example 1 This embodiment provides a positive electrode sheet, its preparation method, and a battery. For example... Figure 1 As shown, the positive electrode includes: Current collector (aluminum foil); A first positive electrode coating is disposed on at least one side surface of the current collector along the thickness direction; the first positive electrode coating comprises lithium iron phosphate material and ternary material A. A second positive electrode coating is disposed on the surface of the first positive electrode coating away from the current collector; the second positive electrode coating comprises ternary material B.
[0060] The lithium iron phosphate material comprises a lithium iron phosphate body and a carbon coating layer covering the surface of the lithium iron phosphate body. The lithium iron phosphate body contains a dopant element Ti at a doping level of 3000 ppm. The carbon coating layer accounts for 1.2 wt% of the mass of the lithium iron phosphate material, and the lithium iron phosphate material accounts for 75 wt% of the sum of the masses of the ternary material A and the lithium iron phosphate material. The repose angle of the lithium iron phosphate material is 40°, and D... V 50 particles with a diameter of 1 μm; The ternary material A is specifically a ternary lithium nickel cobalt manganese oxide material with the chemical formula LiNi. 0.815 Co 0.06 Mn 0.12 Mg 0.005 O2; its cobalt content is 6 mol% (based on the total amount of metals in ternary material A excluding Li), sphericity 0.9, angle of repose 26°, D V 50 particles with a diameter of 6.5 μm; The ternary material B is specifically a ternary lithium nickel cobalt manganese oxide material with the chemical formula LiNi. 0.775 Co 0.1 Mn 0.12 Mg 0.005 O2; its cobalt content is 10 mol% (based on the total amount of metals excluding Li in ternary material B), sphericity is 0.7, D V 50 particles with a diameter of 3.5 μm; The lithium iron phosphate material, ternary material A, and ternary material B are all from Minmetals New Energy Materials (Hunan) Co., Ltd.
[0061] The positive electrode sheet is prepared by a step-by-step coating method; the operation steps include: Lithium iron phosphate material, ternary material A, first binder (PVDF, from Solvay, model 5130), first conductive agent (SP and CNT in a mass ratio of 2:0.8) and dispersant (PVP, from BASF, model K30) were mixed in a mass ratio of 23.75:71.25:2:2.8:0.2, and NMP was added and stirred evenly to obtain a first cathode slurry with a solid content of 68%. The first positive electrode slurry was coated on the surface of the current collector (coating speed 5 m / min), and after drying, the first positive electrode coating was obtained (thickness 75 μm, electrode weight loss rate 0.3% after drying). Ternary material B, second binder (PVDF), and second conductive agent (SP and CNT in a mass ratio of 2:1) were mixed in a mass ratio of 95.5:1.5:3, and NMP was added and stirred evenly to obtain a second positive electrode slurry with a solid content of 73%. The second positive electrode slurry is coated on the surface of the first positive electrode coating away from the current collector (coating speed 5m / min), and after drying, the second positive electrode coating (thickness 35μm, electrode weight loss rate 0.3% after drying) is obtained. After rolling, the positive electrode sheet is obtained.
[0062] The method for preparing the battery includes: assembling the above-mentioned positive electrode sheet, negative electrode sheet, and separator into a dry cell, placing it in an aluminum-plastic bag, baking it, injecting electrolyte, and then performing formation and capacity testing to obtain a soft-pack battery; wherein: The preparation steps of the negative electrode sheet include: mixing graphite, CMC, SBR and SP in a mass ratio of 95:1.5:2:1.5, adding water and stirring evenly to obtain a negative electrode slurry with a solid content of 52%; coating the negative electrode slurry onto the surface of the negative electrode current collector (copper foil) (coating speed 3m / min), drying (the weight loss rate of the electrode sheet after drying is 0.5%), and rolling to obtain the negative electrode sheet.
[0063] The electrolyte is LiPF6 dissolved in a mixed solvent of EC / EMC / DMC with a volume ratio of 1:1:1; wherein the concentration of LiPF6 is 1.5 mol / L.
[0064] The separator comprises a PE base film, and PVDF adhesive layers are disposed on both sides of the PE base film; on the side of the separator facing the positive electrode, an α-type space is provided between the PE base film and the PVDF adhesive layer on that side. Al2O3 ceramic layer.
[0065] Examples 2-17 and Comparative Examples 1-14 Examples 2-17 and Comparative Examples 1-14 respectively provide a positive electrode sheet, its preparation method and battery, with specific implementation methods the same as in Example 1; the differences are shown in Table 1.
[0066] Table 1
[0067] In Table 1, "Lithium iron phosphate percentage" refers to the mass percentage of lithium iron phosphate material in the total mass of lithium iron phosphate material and ternary material A, i.e., lithium iron phosphate percentage = mass of lithium iron phosphate material / (mass of lithium iron phosphate material + mass of ternary material A) × 100%; "cobalt content of ternary material A" refers to the percentage of the molar amount of cobalt element in ternary material A relative to the total molar amount of metal elements (Co+Ni+Mn) in ternary material A, and "cobalt content of ternary material B" refers to the percentage of the molar amount of cobalt element in ternary material B relative to the total molar amount of metal elements (Co+Ni+Mn) in ternary material B, excluding Li.
[0068] In Table 1, the sphericity of the material was determined using scanning electron microscopy (SEM) combined with image analysis software; the test steps included: 1. Take a small amount of the powder to be tested, add ethanol, and ultrasonically disperse until uniform; 2. Place a small amount of liquid in the center of the conductive adhesive on the sample stage; 3. Perform SEM testing after air drying at room temperature; 4. Observe using SEM at 5000x magnification, and randomly select 200 non-overlapping and non-broken particles from different locations for preservation; 5. Import the SEM image into ImageJ software, export parameter data such as A and P, and then apply the formula... The sphericity of a single particle is calculated, and then the average sphericity is obtained by taking the average value.
[0069] The angle of repose of the material was determined by the injection method in GB / T 11986-1989 "Measurement of Angle of Repose of Surfactant Powders and Particles".
[0070] Material D V The particle size of 50 was determined using a laser particle size analyzer; the testing steps included: 1. Take a small amount of the powder to be tested and add it to pure water to disperse it evenly by ultrasonication; 2. Take a small amount of the well-dispersed liquid and transfer it to a Malvern 3000 laser particle size analyzer for testing; read the material D value. V 50 particle size value; 3. Each sample was tested 5 times, and the average value of the results was taken.
[0071] Example 15 Example 15 provides a positive electrode sheet, its preparation method, and a battery, with the specific implementation method being the same as that in Example 1; the difference is that the positive electrode sheet is prepared by co-coating; specifically, a multilayer extrusion coating die is used to simultaneously extrude and coat the first positive electrode slurry and the second positive electrode slurry onto the surface of the current collector; after drying, a current collector, a first positive electrode coating, and a second positive electrode coating are obtained in sequence, and after rolling, a positive electrode sheet is obtained.
[0072] Example 16 Example 16 provides a positive electrode sheet, its preparation method, and a battery. The specific implementation method is the same as that in Example 1; the difference is that the thickness of the first positive electrode coating is 100 μm, and the thickness of the second positive electrode coating is 60 μm.
[0073] Example 17 Example 17 provides a positive electrode sheet, its preparation method, and a battery, with the specific implementation method being the same as in Example 1; the difference being that ternary materials A and B are replaced by ternary lithium nickel cobalt manganese oxide (NCM) with ternary lithium nickel cobalt aluminum oxide (NCA), i.e., ternary material A is LiNi0.815 Co 0.06 Al 0.12 Mg 0.005 O2; Ternary material B is LiNi 0.775 Co 0.1 Al 0.12 Mg 0.005 O 2; The aluminum content is comparable to the manganese content in Example 1.
[0074] Comparative Example 13 Comparative Example 13 provides a positive electrode sheet, its preparation method, and a battery, with the same specific implementation method as Example 1; the difference is that the thickness of the first positive electrode coating is 120 μm, and the thickness of the second positive electrode coating is 70 μm.
[0075] Performance testing The batteries prepared in the above embodiments and comparative examples were used as test samples and the following tests were conducted; the test results are recorded in Table 2.
[0076] 1. Security performance testing Battery safety performance is evaluated using a needle penetration test. The test conditions are as follows: a 5mm diameter steel needle is inserted vertically into the center of the battery's largest surface (usually the front) at a speed of 2mm / min, and the battery is observed to see if it ignites. If the battery does not ignite, it is considered to have passed; if it ignites, it is considered to have failed.
[0077] 2. Ratio Performance Test The rate performance of a battery is evaluated by the ratio of its 5C discharge capacity to its 1C discharge capacity. The test procedure is as follows: First, charge the battery at a constant current of 1C to 4.35V, then charge it at a constant voltage until the current ≤0.05C; after resting, discharge it at a constant current of 1C to 2.5V, and record the capacity C1; next, charge it at a constant current of 1C to 4.35V, then charge it at a constant voltage until the current ≤0.05C; finally, discharge it at a constant current of 5C to 2.5V, and record the capacity C2. The 5C discharge capacity of the battery is calculated using the following formula: 5C discharge capacity (%) = C2 / C1 × 100%.
[0078] 3. Cyclic performance test The cycle performance of a battery is evaluated by its cycle life. The test procedure is as follows: discharge at a constant current of 1C to 2.5V, and rest for 10 minutes; then charge at a constant current of 1C to 4.35V, and charge at a constant voltage until the current is ≤0.05C, and rest for 10 minutes; then discharge at a constant current of 1C to 2.5V, record the initial capacity C0, and rest for 10 minutes; subsequently, perform cycle tests according to the above charge and discharge conditions, and record the discharge capacity C1, C2...C for each cycle. n Capacity retention rate (C) nThe cycle life of the battery is defined as the number of cycles (n) experienced when the percentage (C0×100%) first drops below 80%.
[0079] Table 2
[0080] The data analysis in Table 2 is as follows.
[0081] (1) Influence of sphericity of ternary materials: As can be seen from the comparison between Examples 1-5 and Comparative Examples 1-3, the sphericity of ternary materials needs to be controlled within a reasonable range in order to balance cycle performance and rate performance. When the sphericity is too high (as in Comparative Example 1), the specific surface area of the material is low, resulting in good gradation between particles, reduced electrode porosity, and insufficient electrolyte wetting, leading to deterioration of rate performance. When the sphericity is too low (as in Comparative Example 3), the specific surface area of the material is too large, side reactions increase, and cycle performance deteriorates. In addition, when the sphericity of the ternary material in the second positive electrode coating is higher than that in the first positive electrode coating (as in Comparative Example 2), since the second positive electrode coating is closer to the separator side, it preferentially undergoes charging and discharging, and its rate performance degradation will dominate the overall rate performance of the battery, leading to deterioration of the battery rate performance.
[0082] (2) Influence of ternary material particle size and angle of repose: A comparison of Examples 1, 6-9, and Comparative Examples 4-7 shows that the particle size of the ternary material and the difference in angle of repose between the ternary material and the lithium iron phosphate material need to be controlled within a reasonable range to balance cycle performance and rate performance. When material D... V When the particle size is too large (e.g., in Comparative Example 5), the lithium-ion solid-phase diffusion path increases, leading to a deterioration in rate performance; when material D... V When the particle size is too small (e.g., in Comparative Example 6), the specific surface area increases, side reactions increase, and cycle performance deteriorates. When the particle size of ternary material A increases and the particle size of ternary material B decreases (e.g., in Comparative Example 4), because ternary material B is on the surface of the positive electrode, it has more contact with the electrolyte and is closer to the surface of the negative electrode. Therefore, the performance is closer to the influence of ternary material B, i.e., the rate performance does not change much, but the cycle performance decreases significantly. Furthermore, when the D of ternary material B in the second positive electrode coating... V Material D with a particle size greater than that of ternary material A in the first cathode coating VAt a particle size of 50 μm (e.g., Comparative Example 7), the second positive electrode coating, being closer to the separator, preferentially undergoes charging and discharging. Its rate performance degradation will dominate the overall rate performance of the battery, leading to a deterioration in rate performance. From the perspective of the angle of repose difference, Examples 1 (difference 14°) and Examples 6-9 (difference 10°-20°) all exhibit good overall performance, while Comparative Examples 4-7 show significant degradation in rate or cycle performance. When the angle of repose difference is too small (e.g., Comparative Examples 6 and 7, difference 9°), the flowability difference between the two types of particles is insufficient, increasing the coating of the lithium iron phosphate particles on the surface of the ternary material. This leads to increased breakage and over-discharge of the ternary material particles during rolling, resulting in deteriorated cycle performance. When the angle of repose difference is too large (e.g., Comparative Examples 4 and 5, difference 21°), the flowability difference between the lithium iron phosphate material and the ternary material is too large, resulting in poor dispersion uniformity of the two types of particles in the slurry and electrode, leading to a deterioration in rate performance.
[0083] (3) The effect of cobalt content in ternary materials: As can be seen from the comparison of Examples 1, 10-13 and Comparative Examples 8-11, the cobalt content of ternary materials needs to be controlled within a reasonable range in order to balance cycle performance, rate performance and safety performance. When the cobalt content is too low (as in Comparative Example 11), the safety performance and cycle performance of the battery will be reduced because cobalt plays a role in stabilizing the crystal structure of the ternary material and improving electronic conductivity. When the cobalt content is too high (as in Comparative Example 8), the material cost will increase significantly because cobalt is a precious metal, which is not conducive to mass production and application. In addition, the excessive cobalt content will also lead to a decrease in the specific capacity of the material. Furthermore, when the cobalt content of ternary material B in the second positive electrode coating is lower than that of ternary material A in the first positive electrode coating (as in Comparative Example 9), the cycle performance deteriorates more significantly at a lower cobalt content because the second positive electrode coating is closer to the separator, in direct contact with the electrolyte, and preferentially undergoes charging and discharging with a higher depth of charge and discharge.
[0084] (4) The influence of the proportion of lithium iron phosphate material: As can be seen from the comparison between Examples 1 and 14 and Comparative Examples 12 and 14, the proportion of lithium iron phosphate material in the first positive electrode coating needs to be controlled within a reasonable range in order to balance safety performance and cycle rate performance. When the proportion of lithium iron phosphate material is too low (such as in Comparative Example 12), the insufficient proportion of lithium iron phosphate material will lead to a deterioration in battery safety performance because the structural stability of lithium iron phosphate material is better than that of ternary materials. When the proportion of lithium iron phosphate material is too high, the lithium ion diffusion channel in lithium iron phosphate material has a one-dimensional characteristic, which will limit the insertion and extraction rate of lithium ions, leading to a deterioration in rate performance (such as in Comparative Example 14).
[0085] (5) Effect of coating process: Compared with Example 1 which uses two coatings, Example 15 with dual-die extrusion coating has improved cycle performance, while other performances are comparable. This is because the two-layer interface of dual-die coating is liquid-liquid contact, which has fewer defects than the original solid-liquid contact, thus improving battery cycle performance.
[0086] (6) Effect of coating thickness: Compared with Comparative Example 13, the coating thickness of Examples 1 and 16 gradually increased, and the cycle performance and rate performance decreased. When the electrode thickness exceeded the upper limit, insufficient kinetic performance would induce lithium plating, resulting in a significant deterioration of cycle life. At the same time, the rate performance would also decrease significantly due to kinetic limitation.
[0087] (7) Effects of NMC and NCA: Compared with NCM in Example 1, the cycle performance of NCA used in Example 17 was slightly reduced and the rate performance was slightly improved. The main reason is that aluminum has a slightly lower ability to stabilize the lattice of ternary materials than manganese. Therefore, during long-term cycling, the structural degradation of NCA material is relatively higher than that of NCM. At the same time, the ion diffusion rate is faster and the rate performance of the battery is improved.
[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A positive electrode plate, characterized in that, The positive electrode sheet includes: current collector; A first positive electrode coating is disposed on at least one side surface of the current collector along the thickness direction; the first positive electrode coating comprises lithium iron phosphate material and ternary material A. A second positive electrode coating is disposed on the surface of the first positive electrode coating away from the current collector; the second positive electrode coating comprises ternary material B.
2. The positive electrode sheet according to claim 1, characterized in that, The positive electrode sheet satisfies at least one of the following conditions: (1) The sphericity of the ternary material A is greater than that of the ternary material B; (2) The angle of repose of the ternary material A is smaller than that of the lithium iron phosphate material, and the difference between the two is 10°~20°; (3) The D of the lithium iron phosphate material V 50 particles with a diameter smaller than that of the ternary material B V 50 particle size; (4) The D of the ternary material B V 50 particles with a diameter less than or equal to that of the ternary material A V 50 particle size.
3. The positive electrode sheet according to claim 2, characterized in that, The positive electrode sheet satisfies at least one of the following conditions: (1) The sphericity of the ternary material A is 0.8~1; (2) The angle of repose of the ternary material A is 20°~30°; (3) The D of the ternary material A V 50 particles have a diameter of 5μm to 8μm; (4) The angle of repose of the lithium iron phosphate material is 30°~50°; (5) The D of the lithium iron phosphate material V 50 particles have a diameter of 0.5μm to 2μm; (6) The sphericity of the ternary material B is 0.6~0.8; (7) The D of the ternary material B V The particle size of 50 particles is 2μm~5μm.
4. The positive electrode sheet according to claim 1, characterized in that, Both ternary material A and ternary material B are cobalt-containing ternary materials, and satisfy at least one of the following conditions: (1) The cobalt content in the ternary material A is lower than the cobalt content in the ternary material B; (2) The cobalt content in the ternary material A is 4 mol% to 8 mol% of the total metal content excluding Li in the ternary material A. (3) The cobalt content in the ternary material B is 8 mol% to 12 mol% of the total amount of metals other than Li in the ternary material B.
5. The positive electrode sheet according to claim 4, characterized in that, The chemical formulas of both ternary material A and ternary material B are Li. a Ni b Co c M d N e O f ; Wherein, 0.6≤a≤1.1, 0.5≤b≤0.95, 0.04≤c≤0.12, 0.01≤d≤0.35, 0.001≤e≤0.01, 1.9≤f≤2.1, and b+c+d+e=1, M includes at least one of Mn and Al, and N includes one or more combinations of Mg, Sr, B, Ca, Na, K, Sn, Cu, Ti, Nb, La, Bi, and Zr.
6. The positive electrode sheet according to claim 1, characterized in that, The lithium iron phosphate material includes a lithium iron phosphate body and a carbon coating layer covering the surface of the lithium iron phosphate body. The lithium iron phosphate material satisfies at least one of the following conditions: (1) The mass of the carbon coating layer is 1wt%~2wt% of the mass of the lithium iron phosphate material; (2) The mass of the lithium iron phosphate material is 60wt% to 90wt% of the sum of the masses of the ternary material A and the lithium iron phosphate material.
7. The positive electrode sheet according to claim 6, characterized in that, The lithium iron phosphate material contains doping elements, and the lithium iron phosphate material satisfies at least one of the following conditions: (1) The lithium iron phosphate body contains doped elements; (2) The carbon coating layer contains doped elements; (3) The doping element includes a metallic element; (4) The doping element is selected from at least one of Ti, V, Zr, Mn, Mg, and Al; (5) The doping elements include non-metallic elements; (6) The doping element is selected from at least one of Si, F, N, and Cl; (7) The doping amount of the doping element in the lithium iron phosphate material is 500ppm~3000ppm.
8. The positive electrode sheet according to claim 1, characterized in that, The positive electrode sheet satisfies at least one of the following conditions: (1) The thickness of the first positive electrode coating is greater than the thickness of the second positive electrode coating; (2) The thickness of the first positive electrode coating is 75μm~100μm; (3) The thickness of the second positive electrode coating is 35μm~60μm.
9. A method for preparing a positive electrode sheet, characterized in that, The positive electrode sheet is prepared by step coating or co-coating. The step-by-step coating process includes: Lithium iron phosphate material, ternary material A, first binder, first conductive agent and dispersant are mixed evenly to obtain the first positive electrode slurry; The first positive electrode slurry is coated onto the surface of the current collector and dried to obtain the first positive electrode coating. Ternary material B, second binder, and second conductive agent are mixed evenly to obtain the second positive electrode slurry; The second positive electrode slurry is coated onto the surface of the first positive electrode coating away from the current collector, and then dried and rolled to obtain the positive electrode sheet; The co-coating process includes: Lithium iron phosphate material, ternary material A, first binder, first conductive agent and dispersant are mixed evenly to obtain the first positive electrode slurry; Ternary material B, second binder, and second conductive agent are mixed evenly to obtain the second positive electrode slurry; Using a multi-layer extrusion coating die, the first positive electrode slurry and the second positive electrode slurry are simultaneously extruded and coated onto the surface of the current collector; after drying, the current collector, the first positive electrode coating and the second positive electrode coating are obtained in sequence, and after rolling, the positive electrode sheet is obtained.
10. A battery, characterized in that, The battery comprises a positive electrode sheet as described in any one of claims 1 to 8 or a positive electrode sheet prepared by the preparation method described in claim 9.
